Towards a common terminology for arthropod spatial orientation. Issue 3 (4th May 2021) - Grob, Robin; el Jundi, Basil; Fleischmann, Pauline N.
Abstract : Spatial orientation is essential for all animals that have to successfully change locations during e.g. foraging, homing or migration. Arthropods occupy many different ecological niches and, thus, have evolved a vast number of orientation strategies while moving by air, land, and water. Some of these strategies seem to be rather simple but are perfectly adapted to the behavioural need of an animal. Other strategies are rather complex and require multiple sensory inputs. But what exactly are the fundamental differences between the various strategies and can we define a common terminology that facilitates debates on the underlying orientation strategies exhibited by arthropods? Here, we review examples of spatial orientation behaviours employed by arthropods and provide a unified terminology about their orientation strategies. In addition to behavioural findings, we also consider the current knowledge of the underlying neuronal network to provide a broad and common terminology of orientation strategies. According to our terminology, "spatial orientation" is any kind of directed behaviour. These directed behaviours can be divided into four types of spatial orientation. Non-compass orientation is based on local directional information, e.g. taxis. Compass orientation is based on global compass information, such as the use of a magnetic compass, or a time-compensated sky compass. Egocentric navigation is based on positional information collected en route, e.g. path integration. Geocentric navigation is based on positional information collected on site, e.g. map-based navigation. We highlight examples of diverse arthropod species and discuss controversial explanations of arthropod behaviour in space.